Highlighting the Potential of LyeTx I, a Peptide Derived from the Venom of the Spider Lycosa erythrognatha, as a Potential Prototype for the Development of a New Antimicrobial Against Carbapenem-Resistant Klebsiella pneumoniae - William Gustavo Lima; Amanda Souza Félix; Felipe Rocha da Silva Santos; Fernanda de Lima Tana; Amanda Neves de Souza; Rodrigo Moreira Verly; Maria Elena de Lima (Pharmaceuticals)
Background: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is a multidrug-resistant (MDR) gram-negative bacterium frequently involved in hospital-acquired pneumonia. The infection caused by this superbug has spread quickly in health centers worldwide, leading to high mortality rates. Due to this emerging scenario, the World Health Organization has categorized CRKP as the highest-priority species for the development of new compounds. In this context, antimicrobial peptides (AMPs) stand out as prototypes for alternative antimicrobials against superbugs, including CRKP. Objectives: We aimed to describe the antibacterial effect of an AMP (LyeTx I), derived from the venom of the spider Lycosa erythrognatha, against CRKP in vitro and in a murine pneumonia model. Results: LyeTx I showed antibacterial effects against all the CRKP clinical isolates tested, with a minimum inhibitory concentration (MIC) range of 2–8 µM and a minimum bactericidal concentration (MBC) range of 2–16 µM. The microbial anionic membrane was the primary target of LyeTx I, which acts by displacing divalent cations bound to this structure in a manner similar to that of polymyxins. Notably, LyeTx I displayed significant lytic activity against mimetic membranes, indicating its potential to disrupt bacterial cell integrity. In in vivo assays, the LyeTx I peptide proved to be safe at a dose of 10 mg/kg. In addition, intraperitoneal use of LyeTx I reduced the bacterial load and inflammation in the lungs of animals infected with a hypervirulent strain of CRKP. Conclusions: These results indicate that LyeTx I is a potential prototype for the development of new antibacterials against MDR species, such as CRKP.